A CONCEPTUAL FRAMEWORK FOR HALAL SMEs DIGITAL TRANSFORMATION: OVERCOMING PLATFORM DEPENDENCY THROUGH FINTECH-ENABLED DIRECT-TO-CONSUMER STRATEGIES - Shafira, Alfina; Said, Muhammad; Hosen, Muhammad Nadratuzzaman; Yama, Indo; Rizal, Sofyan (LPPM Universitas Jambi, 2026)
This study aims to develop a comprehensive conceptual framework to transform halal SMEs from platform dependency to digital autonomy through independent Direct-to-Consumer (D2C) websites, supported by Sharia-compliant fintech. This study employs a bibliometric review, drawing on 120 high-quality publications (30 papers per search query) from the Scopus and Web of Science databases. VOSviewer software was used to perform co-occurrence analysis of author and index keywords, generating network, overlay, and density visualizations. The VOSviewer analysis identified 23 key items divided into 3 main clusters with 207 links and a total link strength of 902: (1) Red Cluster – Supporting Technologies for Standalone Websites (website, platform, e-commerce, user, application); (2) Green Cluster – Fintech Innovation in the Halal Digital Ecosystem (fintech, innovation, data, evidence, role); and (3) Blue Cluster – Comparison of D2C Business Models (performance, company, time, resource, effect). The overlay visualization indicated that websites (2018.0), e-commerce (2018.5), fintech (2018.5), and innovation (2018.5) were relatively new research areas. The proposed three-stage framework—Market Dependency, Hybrid Transition, and Digital Autonomy—integrates appropriate fintech instruments (Murabahah for digital asset development, revenue-based financing for marketing, and Mudharabah for growth). Novelty: This study offers the first bibliometric mapping of the intersection between halal SMEs, D2C models, and Sharia fintech, proposing an integrated framework that bridges technical, financial, and institutional dimensions. Implications: The framework provides practical guidance for halal entrepreneurs, fintech providers, and policymakers to reduce platform dependency and achieve digital autonomy.